Vitamin A deficiency is prevalent in children less than 5 years of age in Nigeria - Maziya-Dixon, B.B.; Akinyele, I.O.; Sanusi, R.A.; Oguntona, T.E.; Nokoe, S.K.; Harris, E.W. (2006)
Vitamin A deficiency (VAD) is a serious and widespread public health problem in developing countries. We conducted a nationwide food consumption and nutrition survey in Nigeria to help fomulate strategies to address VAD, among other deficiencies. One objectives was to assess the vitamin A status of children,5 y old. A total of 6480 households with a mother and child,5 y old were randomly sampled. Blood samples were collected by venipuncture and processed to obtain serum for measurement of retinol concentration by HPLC. Nationwide, 29.5% of children,5 y old were vitamin A deficient (serum retinol,0.70mmol/L). The proportions of children with VAD differed among the agroecological zones; incidences were 31.3% in the dry savanna, 24.0% in the moist savanna, and 29.9% in the humid forest (P,0.001). More children (P,0.05) with severe deficiency (serum retinol,0.35mmol/L) lived in the humid forest (7.1%) than in the dry (3.1%) or moist savanna (2.4%). The distribution of VA in children, 5 y old was 25.6% in the rural sector, 32.6% in the medium, and 25.9% in the urban sector (P,0.05). In conclusion, VAD is a severe public health problem in Nigeria. Although the proportion of children with low serum vitamin A levels varies agroecologically and across sectors, it is an important public health problem in all zones and sectors.